2016
DOI: 10.1111/his.12931
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ezrin in human intrahepatic cholangiocarcinoma is associated with ectopic expression of E‐cadherin

Abstract: Ezrin is down-regulated during cholangiocarcinogenesis, and its loss results in a more aggressive phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, these data indicated that Ezrin may also serve as a tumour suppressor. 29 The discordance between these studies suggested that the effects of Ezrin in different tumours may be different. Ezrin overexpression promotes BC progression via AKT signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these data indicated that Ezrin may also serve as a tumour suppressor. 29 The discordance between these studies suggested that the effects of Ezrin in different tumours may be different. Ezrin overexpression promotes BC progression via AKT signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Relocalisation of adherens junction component E-Cadherin from BEC membranes, implicates reduced cell adhesion and strongly supports this notion since mis-regulation of E-Cadherin levels is a hallmark of biliary diseases. BEC-specific deletion of E-Cadherin in mice causes cholangitis and cancer(Nakagawa et al ., 2014), while in biliary atresia and intrahepatic cholangiocarcinoma it is aberrantly expressed in BECs and hepatocytes (Guedj et al, 2016). The loss of E-cadherin at BEC membranes is also reminiscent of epithelial-to-mesenchymal transition, where E-cadherin reduction and upregulation of N-cadherin results in acquisition of mesenchymal migratory behaviours (Lamouille et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding in breast cancer showed that high Ezrin and low E-cadherin expression were more related to lymph node metastasis and poor prognosis [ 93 ]. In contrast, in intrahepatic cholangiocarcinoma, lack of or low Ezrin expression is associated with ectopic expression of E-cadherin and may coincide with the activation of an EMT-like process [ 94 ].…”
Section: Ezrin Interacts With Metastasis-related Proteinsmentioning
confidence: 99%